EVALUASI MUTU PELAYANAN KEFARMASIAN PADA MASA PANDEMI COVID-19 DI RUMAH SAKIT SANTA ANNA KOTA KENDARI - Sabarudin Sabarudin; Dian Munasari Solo; Muhammad Jefriyanto B; Nurramadhani A Sida; Wa Ode Asdia (Journal Publicuho, 2020)
Quality is compliance with predefined standards or following the requirements. Minimum Service Standards health in hospitals is very important to measure the hospital's performance of health services. This study aims to describe the quality of service at the Pharmacy Installation at Santa Anna Hospital, Kendari City during the Covid-19 pandemic based on five indicators of minimum pharmaceutical service standards are waiting time for drug services, the absence of errors in drug administration, writing prescriptions according to the formulary, patient satisfaction and availability of SOP (Standard Operating Procedures). This study is observational research which is descriptive used cross sectional design. The sample was outpatients for 90 samples at Santa Anna Hospital, Kendari City, who fulfill the inclusion criteria. Instruments used questionnaire sheets and observation sheets. The results showed that the indicator of waiting time for concocted drugs and non-concocted drugs was 8 minutes and 4 minutes, respectively. There was no error in administering medications (100%). The suitability of prescription writing to the National Formulary was 99.73%, patient satisfaction to tangible dimensions and reliability dimensions were 82.23% and 84.84%, respectively. The responsiveness dimension was 79.65%, the assurance dimension was 83.54%, and the empathy dimension was 85.48%, and the availability of the standard operating procedure was 63.64%. This study's pharmacy installation at Santa Anna Hospital in Kendari City has not fulfilled the predetermined Minimum Service Standards.